2022
DOI: 10.1589/jpts.34.791
|View full text |Cite
|
Sign up to set email alerts
|

Influence of patients’ walking ability at one-week post-proximal femur fracture surgery on the choice of discharge destination in Japan

Abstract: With the innovation of healthcare delivery systems, a need for early determination of patients' discharge outcomes arises after proximal femur fracture surgery, to reduce the burden on healthcare infrastructure. Several studies have examined the extent of walking ability early in the postoperative period to predict the outcome destination. In this study, as an additional validation of these studies, we examined the effect of walking ability on the hospital discharge prognosis of patients in the first week afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Many studies have shown that ADL on admission and discharge were predictors of discharge destination of stroke patients [ 9 , 19 , 20 ]. The discharge destination predictors have been reported for several diseases, including spinal cord injury and post-proximal femoral fracture [ 21 , 22 ]. Regarding bone metastasis, a previous retrospective observational study reported that the discharge destination was associated with discharge ADL, and the cut-off value of the Barthel Index was 72.5 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that ADL on admission and discharge were predictors of discharge destination of stroke patients [ 9 , 19 , 20 ]. The discharge destination predictors have been reported for several diseases, including spinal cord injury and post-proximal femoral fracture [ 21 , 22 ]. Regarding bone metastasis, a previous retrospective observational study reported that the discharge destination was associated with discharge ADL, and the cut-off value of the Barthel Index was 72.5 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…highlights the relation of the staying with co-residents or family members and walking ability after 1 week of PFF surgery i.e., Barthel Index at discharge of Home group v/s Hospital referred group (75.6 ± 22.7 )v/s(58.0 ± 24.6), p value<0.01,odds ratios are walking ability one week after surgery 1.9, p <o.o5,staying with Co-residents 4.6, p < o.o1. [24] Suguru Ohsawa et.al study suggest that all the patients in the assertive rehabilitation group recovered their ability to walk (FIM score) to some extent, while those in the conventional group did not. Ambulationd (FIM): Assertive method (18.29+/-7.9) v/s Conventional method (9.49+/-4.3, p-value=0.00135).…”
Section: Loss Of Workdaysmentioning
confidence: 95%
“…study from showed that Japan's long-term care insurance system that allow elderly people to receive appropriate support in their daily living according to their level of independence and physical and mental functions which is not present in developed country of world. [24] Comparing studies from developed to developing country the study of Kyle T. Judd et.al based in USA showed the average cost of the early intervention per patient was $49,900 and the average cost of late intervention per patient was $65,300 (p= 0.0086) [25] while R. Aigner et.al. study based in India showed that the mean total acute care costs per patient was 8853 € ± 5676 €.…”
Section: Patient Demographics and Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations